Eosinophilic enteritis caused chronic partial small intestinal obstruction: a case report and review of the literature - Yamada S. (2014)
This is the case-report of a rare cause of chronic small intestinal obstruction by eosinophilic enteritis. A 53-year-old woman presented with an 8-month history of severe intermittent abdominal colick associated with malnutrition, weight loss, and bowel habit change. Several investigations were done but failed to demonstrate the cause. Exploratory laparotomy was therefore performed and the cause of partial small bowel obstruction was found to be eosinophilic enteritis.